2007
DOI: 10.1093/aob/mcm107
|View full text |Cite
|
Sign up to set email alerts
|

Do we Underestimate the Importance of Leaf Size in Plant Economics? Disproportional Scaling of Support Costs Within the Spectrum of Leaf Physiognomy

Abstract: These data demonstrate that variation in leaf size is associated with major changes in within-leaf support investments and in large modifications in integrated leaf chemical and structural characteristics. These size-dependent alterations can importantly affect general leaf structure vs. function scaling relationships. These data further demonstrate important life-form effects on and climatic differentiation in foliage support costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(183 citation statements)
references
References 70 publications
11
157
2
5
Order By: Relevance
“…The negative relationship was strongest in LiC, and smaller and not significant in LiN, indicating that extent of the trade-off may be conditiondependent. A similar negative relationship was recently shown between N percentage, as a proxy of protein concentration, and the dry to fresh mass ratio in 122 vascular plant species 39 as well as between N content and leaf weight in barley 40 , demonstrating the generality of the trade-off between size and protein concentration within and across species, as well as its importance in an ecological context and in crop plants.…”
Section: Resultssupporting
confidence: 79%
“…The negative relationship was strongest in LiC, and smaller and not significant in LiN, indicating that extent of the trade-off may be conditiondependent. A similar negative relationship was recently shown between N percentage, as a proxy of protein concentration, and the dry to fresh mass ratio in 122 vascular plant species 39 as well as between N content and leaf weight in barley 40 , demonstrating the generality of the trade-off between size and protein concentration within and across species, as well as its importance in an ecological context and in crop plants.…”
Section: Resultssupporting
confidence: 79%
“…The needles and scale leaves of conifers are successful in high light but there are clear limits on the utility of this hydraulic design where competition for light is intense in the forest understorey. A general trend of increased leaf size in plants grown under low light (Givnish 1987;Abrams and Kubiske 1990) suggests that the economic benefits of large leaf size for reducing the proportion of mechanical support costs (Westoby and Wright 2003;Niinemets et al 2007a) become important in the understorey (Saldaña et al 2007). Because of the hydraulic constraint on maximum width, needles can increase in size only by increasing length.…”
Section: Needles and Scalesmentioning
confidence: 99%
“…Explicit determination of the construction costs of venation (cf. Niinemets et al 2006Niinemets et al , 2007aNiinemets et al , 2007b should be a priority for future work on leaf hydraulics. Formulating the details of cost v. benefit as it applies to hydraulic investment and photosynthetic gain will provide a basis for interpreting patterns of leaf hydraulic architecture in extant natural vegetation as well as in fossil floras.…”
Section: Hydraulic Supply and Leaf Economicsmentioning
confidence: 99%
“…However, right-skewed leaf size frequency distributions may also reflect biologically prevalent allometric trends whose adaptive significance remains problematic or obscure. For example, it has been suggested that plant height and twig size have significant effects on leaf size optimization (e.g., Ackerly and Donoghue 1998;Cornelissen 1999;Westoby and Wright 2003;Sun et al 2006;Xiang et al 2009) and that large leaves require disproportionally more mechanical tissues (both within the leaf lamina and within subtending stems) than do smaller leaves (Givnish 1984;Niklas 1999;Niinemets and Kullm 1999;Niinemets et al 2006Niinemets et al , 2007aLi et al 2008). Due to these allometry relationships, small leaves may confer adaptive benefits indirectly, i.e., the focus of natural selection may not be directly on leaf size per se.…”
Section: Leaf Size Frequency Distributions Within Habitatsmentioning
confidence: 99%
“…However, for interspecific variation within habitats with similar macroclimatic conditions, leaf size has been assumed to be a neutral trait confounded by community phylogenetic composition, or simply an allometric consequence of plant size, anatomy, or architecture. For example, leaf size has been found to be significantly correlated with plant height (Ackerly and Donoghue 1998;Cornelissen 1999), subtending twig size (Brouat et al 1998;Westoby and Wright 2003;Sun et al 2006), within-leaf biomass allocation and physiology (Niinemets et al 2006(Niinemets et al , 2007aNiklas et al 2007;Li et al 2008), and seed or fruit size (Ackerly and Donoghue 1998;Cornelissen 1999;Westoby and Wright 2003).…”
Section: Introductionmentioning
confidence: 99%